The wave concept in electromagnetism and circuits : theory and applications - Baudrand, Henri; Titaouine, Mohammed; Raveu, Nathalie (Waves series., 2016)
This book provides background information for students and researchers using mathematical equations leading to a better understanding of electromagnetic behavior. It introduces in detail a new formulation of the integral methods and a set of applications applicable to a variety of electromagnetic domains.